A Novel Red‐Blood‐Cell‐Shaped Pectin‐Oligochitosan Hydrogel System. (1st April 2014) - Harvestine, Jenna Nicole; Mikulski, Brandon Anthony; Mahuta, Kirsten Mary; Crouse, James Zachary; Guo, Xiaoru; Lee, Jung Chull; Midelfort, Katarina Senn; Chen, Junhong; Zhang, Wujie
<x xml:space="preserve">Abstract</x> The biocompatible red‐blood‐cell‐shaped pectin–oligochitosan hydrogel capsule offers a large surface area to volume ratio, which improves transport capacity compared to the spherical one. This hydrogel capsule system can be used not merely for controlled delivery/release of bioactive agents, cell immobilization, or cell encapsulation towards regenerative medicine and tissue engineering, but also for creating artificial red blood cells/artificial blood. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>